'The ISIS files': Learning the lessons of history?. Issue 1 (1st June 2020) - Brand, Laurie A.; Tucker, Judith E.
An examination and critique of the New York Times (NYT) publication of 'The ISIS files', a series of articles and podcasts compiled by reporter Rukmini Callimachi, based on more than 15, 000 documents removed from Iraq without permission from the relevant Iraqi authorities. The NYT reportage featured a number of these documents, published in unredacted form, demonstrating a complete disregard for the myriad legal, professional, ethical and moral issues involved. Such issues have been aired in recent years in relation to the handling of other collections of documents arising from the US invasion. This intervention examines the use of these documents, their disposition and future access, arguing that the actions of the NYT represented a neo-imperial mindset directly impacting not only the documents, but also their use in knowledge production. Such production has seen Iraqis denied access to their cultural property as well as the opportunity to control their own records and write their own histories.